Synthesis of Some Novel [2-(substituted phenoxyacetylamino)]-5(β-naphthoxymethylene)-1-3,4-thiadiazoles as potential Fungicides - G.H. Zaidi, Mohd. (Asian Journal of Chemistry, 2010)
A series of [2-(substituted phenoxyacetylamino)]-5-(β-naphthoxymethylene)-1,3,4-thiadiazoles have been synthesized. All such compounds have shown appreciable antifungal activity against two fungi viz. A. niger and H. oryzae.